Critical force during tethered swimming for the evaluation of aerobic capacity and prediction of performances in freestyle swimming - Marcelo Papoti; Ricardo Vitório; Gustavo Gomes Araújo; Luiz Eduardo Barreto Martins; Sérgio Augusto Cunha; Claudio Alexandre Gobatto (Universidade Federal de Santa Catarina, 2010)
The present study investigated the relationship of critical force (Fcrit) with lactate threshold (LLNA) and the intensity corresponding to VO2max (iVO2max) in tethered swimming (TS), and their correlation with maximal performance in 400-m (V400) and 30-min (VT30) freestyle swimming (FS). Seven swimmers were submitted to a TS incremental test for the determination of LLNA and iVO2max. For the determination of Fcrit, the swimmers performed four exercises to exhaustion at intensities (F) corresponding to 87%, 104%, 118% and 134% of iVO2max for the calculation of time limits (Tlim). Fcrit corresponded to the linear coefficient of the ratio between F and 1/tlim. The maximal performance in FS corresponded to the mean velocity obtained during maximal exercise of 400-m and 30-min crawl swimming. Fcrit (51.97 ± 4.02 N) was significantly lower than iVO2max (60.21 ± 8.73 N) but not than LLNA (45.89 ± 8.73). Fcrit was significantly correlated with iVO2max (0.97), LLNA (0.88), V400 (0.85), and VT30 (0.86). These data suggest that Fcrit can be used for the determination of aerobic capacity, prescription of a TS training program, and prediction of performance in FS.